THE CONDITIONS OF HIGHER EDUCATION IN SOMALIA UNTIL 2000– A HISTORICAL STUDY - Lect. Dr. Sulaf Abdulrahman Naji Halboun (Scholars Digest Publishing, 2024)
Somalia is considered one of the countries in the African continent, holding a strategic position in various political, economic, and social aspects. It was colonized by both the British and the Italians and was divided by European colonization into five parts before experiencing independence in 1960. The impact of colonization on all systems, including the educational aspect, was significant. Higher education in Somalia was relatively nonexistent, with no unified educational system or curricula serving the Somali society. The Somali people suffered from ignorance, illiteracy, and the delay in establishing higher education until independence, after which the phase of establishing the National University in Somalia began. The aim of the current research is to trace the conditions of higher education in Somalia until 2000 and confirm the hypothesis that education in general, and higher education in particular, faced several challenges, especially during the colonial era and its aftermath, which affected the education system. There was an educational vacuum due to the absence of the national government, and this hypothesis was reinforced by the following questions: What was the education system like in Somalia? What universities were established in Somalia? What was the impact of the civil war on the higher education sector? The current research focused on exercising caution and precision in dealing with the information obtained within the principles of the historical scientific research methodology based on analysis, inference, and logical linkage of events while maintaining the context of time and place, as they have an impact on shaping historical events.
Keywords: conditions, higher education, historical.